Biogás: vetor energético em uma agroindústria na cidade de Pombal/PB - Souza Neto, José Joaquim de (2021)
Solid residues arising from anthropic activities, such as agriculture, generate serious environmental disturbances, due to the large percentage of organic material in their composition. Therefore, it becomes essential the use of technologies for its treatment. Then, biodigesters prove to be an effective option for reducing the organic load. Perspective, that was observe in the agroindustry Bolo das Oliveiras, in the city of Pombal - PB, where a sertanejo biodigester is installed. Thus, this work seeks to maximize the biogas production, coming from the same. The investigation took place between July of 2020 and January of 2021, totalizing 210 days. The biodigester was fed daily with two types of dilution. In the first phase, 100 kg of bovine dung diluted in 200 liters of water, 1: 2 ratio, were inserted. In the second part of the experiment, 150 kg of manure was used, diluted in 150 liters of water, 1: 1 ratio. In both phases the hydraulic retention time of 45 days was adopted, after that period analyzes were performed fortnightly until the 210th day. The analysis of the affluent and the effluents embraces the physical and chemical, as well as the qualification and quantification of the methane produced in both phases. The results obtained showed few variations, with regard to the substrates, which can be associated with the incomplete digestion of the organic mass in both phases. The biogas production showed a flame of good quality during the 210 days of investigation. However, phase 2 was more efficient in terms of methane production, being compatible with what is indicated in the literature, making the equipment even more efficient from an environmental, economic and social point of view. Thus, increasing the income of families associated with the Bolo das Oliveiras agroindustry with the reduction of costs in the production of bread and cakes.